Evaluasi Penerapan ISPS Code di MV Oriental Jade - Himawan, Zidan Alwi; Sriantini, Ari; Listriyawati, Nyoman Ardiana (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
The implementation of the International Ship and Port Facility Security (ISPS) Code is a crucial effort to ensure ship security, particularly when vessels are berthed or anchored in high-risk areas. However, in practice, not all ships apply these standards optimally. This study aims to evaluate the application of the ISPS Code in watchkeeping operations aboard MV Oriental Jade, particularly after a theft incident that occurred while the vessel was anchored at Belawan Port. This research employs a qualitative descriptive approach with a case study method. Data were collected through observation, interviews with ship officers, and supporting documentation. The results indicate that although the ship's watchkeeping procedures formally adhere to the ISPS Code and the STCW 1978 Amendment 2010, practical implementation remains suboptimal. Several challenges were identified, including limited personnel, crew fatigue, lack of security training, and insufficient supporting facilities such as CCTV and communication devices. Security improvement efforts onboard remain reactive and lack systematic structure. This study recommends regular training, proper supervision, and the provision of adequate supporting equipment to ensure the effective and sustainable implementation of the ISPS Code onboard.